2017
DOI: 10.3390/ijms18091994
|View full text |Cite
|
Sign up to set email alerts
|

The Semi-Synthetic Peptide Lin-SB056-1 in Combination with EDTA Exerts Strong Antimicrobial and Antibiofilm Activity against Pseudomonas aeruginosa in Conditions Mimicking Cystic Fibrosis Sputum

Abstract: Pseudomonas aeruginosa is a major cause of chronic lung infections in cystic fibrosis (CF) patients. The ability of the bacterium to form biofilms and the presence of a thick and stagnant mucus in the airways of CF patients largely contribute to antibiotic therapy failure and demand for new antimicrobial agents able to act in the CF environment. The present study investigated the anti-P. aeruginosa activity of lin-SB056-1, a recently described semi-synthetic antimicrobial peptide, used alone and in combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 62 publications
1
28
0
Order By: Relevance
“…Differently from artificial sputum medium, patients' sputum contains host/bacterial components such as cell-derived factors, normal flora, inflammatory mediators, proteases, or peptidases that may exert an additional inhibitory effect on the peptide's activity. Nevertheless, herein, we showed that the combination of lin-SB056-1 and EDTA at sub-active and non-cytotoxic concentrations [16,27] determined a significant reduction in P. aeruginosa load in sputa of PCD chronically infected patients, despite certain differences in the level of reduction among different sputum samples being observed. Such differences are not surprising considering that inter-patient variables (e.g., clinical stage and severity of lung infection, bacterial load, sputum sample composition, and consistency) were not standardized in our experiments, in the attempt to mimic conditions found during the actual antimicrobial therapy.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Differently from artificial sputum medium, patients' sputum contains host/bacterial components such as cell-derived factors, normal flora, inflammatory mediators, proteases, or peptidases that may exert an additional inhibitory effect on the peptide's activity. Nevertheless, herein, we showed that the combination of lin-SB056-1 and EDTA at sub-active and non-cytotoxic concentrations [16,27] determined a significant reduction in P. aeruginosa load in sputa of PCD chronically infected patients, despite certain differences in the level of reduction among different sputum samples being observed. Such differences are not surprising considering that inter-patient variables (e.g., clinical stage and severity of lung infection, bacterial load, sputum sample composition, and consistency) were not standardized in our experiments, in the attempt to mimic conditions found during the actual antimicrobial therapy.…”
Section: Discussionmentioning
confidence: 55%
“…EDTA is prescribed in a number of clinical conditions demonstrating high tolerability (up to 2 g once a week, intravenously injected) and efficacy [15]. Recently, we demonstrated that the optimized semi-synthetic antimicrobial peptide lin-SB056-1 in combination with EDTA is able to exert a synergistic bactericidal effect against P. aeruginosa in an artificial sputum medium resembling CF sputum [16]. Similarities and differences between CF and PDC sputum have been reported.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…Overall, these findings suggest that the high lipophilic outer membrane of Gram-negative bacteria may function as an efficient barrier against hydrophilic macromolecules such as Ch-derivatives. Combining Ch-derivatives with agents (such as EDTA) able to destabilize the outer membrane of Gram-negative bacteria as well as to sequester positively charged medium components could help in increasing their activity against this group of bacteria [35]. However, a contrasting study, aiming at correlating the antibacterial activity of Ch and the surface characteristic of bacterial cell wall, found that the negative charge on the cell surface of Gram-negative bacteria (P. aeruginosa, Salmonella typhimurium and E. coli) was higher than that of Gram-positive one (Staphylococcus aureus and Streptococcus faecalis) resulting in more Ch adsorbed and higher inhibitory effect against the Gram-negative bacteria [36].…”
Section: Antibacterial Activity Toward P Aeruginosa and S Epidermidismentioning
confidence: 99%